Is a Return To Office a Return To Creativity? Requiring Fixed Time In Office To Enable Brainstorms and Watercooler Talk May Not Foster Research Creativity - Xu, Tianna; Sarkar, Advait; Rintel, Sean (CHIWORK 2023, 2023)
In the aftermath of the Covid-19 pandemic, many professionals, including researchers, have transitioned into hybrid work. One concern arising from this transition is the cost to creativity in an environment of variable co-presence. We interviewed 24 researchers fromseveral disciplines and varying levels of seniority, across 7 research labs in academia and industry about their hybrid work patterns and sources of creativity. Co-present ‘brainstorming’ and serendipitous ‘watercooler’ conversations are both often cited as argumentsfor mandating co-located work patterns in research organisations. Contrary to the dominant account which associates co-presence with increased creativity, we find that the flexibility of hybrid work, and carefully managed co-present interactions punctuating a regime of focused individual work, is the main catalyst of creativity. We find that the ‘problem-oriented discussion’ over time is a more powerful pattern for researcher collaboration than the ‘brainstorm’, that these discussions benefit greatly from the freedom to choose work locations afforded by hybrid work. We also find that serendipitous ‘watercooler’ conversations, while reported as valuable for collegiality, are reported as less valued for their contribution to creativity. We suggest that scheduling time in office should extend temporalities beyond the weekly cadence, and that tools and timing for serendipitous productivity and serendipitous collegiality do not necessarily have to be coupled.